Understanding learners’ metacognitive experiences in learning to write in English as a foreign language: A structural equation modeling approach - Sun, Qiyu; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
Many researchers have acknowledged the role of metacognition in facilitating learning to write in English as a foreign language (EFL). Although research on metacognition has explored learners’ metacognitive knowledge and metacognitive strategies in the field of EFL writing, little is known about the nature of learners’ metacognitive experiences in EFL writing. To fill such an important gap, this study was designed to assess EFL learners’ metacognitive experiences before, during, and after writing. Data were collected from a total of 760 undergraduates through three self-report questionnaires and a writing task. Results from quantitative analyses showed four subcategories of EFL learners’ metacognitive experiences in writing: metacognitive feeling, metacognitive judgments/estimates, online task-specific metacognitive knowledge, and online task-specific metacognitive strategies. Based on the empirical evidence, we propose a model of metacognitive experiences in EFL writing. Theoretical, methodological, and pedagogical implications are discussed.